Acute apnea swimming: Metabolic responses and performance - Guimard, A.; Prieur, F.; Zorgati, H.; Morin, D.; Lasne, F.; Collomp, K. (The Journal of Strength and Conditioning Research, 2014)
Competitive swimmers regularly perform apnea series with or without fins as part of their training, but the ergogenic and metabolic repercussions of acute and chronic apnea have not been examined. Therefore, we aimed to investigate the cardiovascular, lactate, arterial oxygen saturation and hormonal responses to acute apnea in relation to performance in male swimmers. According to a randomized protocol, 15 national or regional competitive swimmers were monitored while performing four 100-m freestyle trials, each consisting of four 25-m segments with departure every 30 seconds at maximal speed in the following conditions: with normal frequency breathing with fins (F) and without fins (S) and with complete apnea for the four 25-m segments with (FAp) and without fins (SAp). Heart rate (HR) was measured continuously and arterial oxygen saturation, blood, and saliva samples were assessed after 30 seconds, 3 minutes, and 10 minutes of recovery, respectively. Swimming performance was better with fins than without both with normal frequency breathing and apnea (p < 0.001). Apnea induced no change in lactatemia, but a decrease in arterial oxygen saturation in both SAp and FAp (p < 0.001) was noted and a decrease in HR and swimming performance in SAp (p < 0.01). During apnea without fins, performance alteration was correlated with bradycardia (r = 0.63) and arterial oxygen desaturation (r = -0.57). Saliva dehydroepiandrosterone was increased compared with basal values whatever the trial (p < 0.05), whereas no change was found in saliva cortisol or testosterone. Further studies are necessary to clarify the fin effect on HR and performance during apnea swimming.